2000
DOI: 10.1159/000028346
|View full text |Cite
|
Sign up to set email alerts
|

Renal Vascular Reactivity to P<sub>2</sub>-Purinoceptor Activation in Spontaneously Hypertensive Rats

Abstract: This study was performed to determine the possible contribution of an imbalance between P2X (vasoconstriction) and P2Y (vasodilation)-purinergic reactivity to the increased vascular resistance of spontaneously hypertensive rats (SHR). The vasoactive responses to α,β-methylene ATP and 2-methylthio ATP specific agonists, respectively, for P2X and P2Y purinergic receptors were characterized in isolated perfused kidneys from Wistar Kyoto (WKY) and SHR. To analyze P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In contrast, ATP causes vasodilatation when baseline renal vascular resistance is high. This reflects P2Y-mediated production of NO [86]. More recent data have shown vasoactive actions of P2X4 and/or P2X7 in the rat renal artery [242].…”
Section: Physiological Responses In the Glomerulus And Renal Vasculaturementioning
confidence: 72%
“…In contrast, ATP causes vasodilatation when baseline renal vascular resistance is high. This reflects P2Y-mediated production of NO [86]. More recent data have shown vasoactive actions of P2X4 and/or P2X7 in the rat renal artery [242].…”
Section: Physiological Responses In the Glomerulus And Renal Vasculaturementioning
confidence: 72%
“…For obvious ethical reasons, these investigations are not possible in normotensive individuals. However, in a hypertensive animal model (spontaneously hypertensive rat), purinergic reactivity and nitric-oxide-induced vasodilatation were well preserved [28]. Secondly, the study design allowed only one infusion procedure per patient.…”
Section: Discussionmentioning
confidence: 99%
“…In those experiments in which ATP caused an increase in [Ca 2ϩ ] i , a second ATP application led to nearly an identical response (Ͼ95%) if there was Ն15 min between ATP applications. Shorter time intervals between applications resulted in smaller increases in [Ca 2ϩ ] i , presumably the result of receptor desen- sitization (16,32). For the studies shown in Figure 2A, a control ATP-mediated increase in [Ca 2ϩ ] i was first obtained, followed by adenosine, ATP, UTP, ADP, or 2Mes-ATP administered in a random order.…”
Section: Statistical Analysesmentioning
confidence: 94%